Thermal shock resistance of additively manufactured gas-permeable SiO2 ceramic structures for HIP-quench applications. Issue 2 (February 2023) - Brackmann, Lukas; Liu, Xiaotian; Ruttert, Benjamin; Weber, Sebastian
Abstract: The increasing demand for hot isostatic pressing (HIP) means that a reliable and efficient operation of modern HIP units with fast cool capability is indispensable. A key factor for efficient operation is the ceramic crucible used as the load basket. Its task is to keep as much of the HIPed parts as possible effectively within the hot zone and to prevent them touching the furnace wall. This work focuses on designing a gas-permeable ceramic structure with a high thermal shock resistance that can be scaled up to a load basket for future HIP applications. Stereolithography (SL) 3D printing of a ceramic resin is employed to build various scalable framework structures inspired by nature and by existing engineering applications. Thermal shock tests with water quenching reveal that framework structures with evenly distributed triangular bracings offer the highest flexural strength, whereas auxetic structures are best at retaining their flexural strength after thermal shock. Highlights: Gas-permeable ceramic structures are manufactured via stereolithography. The thermal shock resistance of the structures is evaluated by water-quenching tests. Low wall-thickness and a high number of bracings increase the thermal shock resistance. Gas-permeable structures retain higher strength after thermal shock than bulk-specimens. The thermophysical properties of the additively manufactured ceramic are measured.